The Effect of Human Resource Quality, Work Environment, and Work Safety on Employee Performance - Ariani, Dera; Habibi, Ahmad; Susanti, Yeni (Journal of Economics and Social Sciences (JESS), 2025)
At this time, the level of competition between companies is increasing and getting tougher, so every company is required to maximize the performance of its employees in the face of continuous competition. Just like the Regional Office of DJBC Sumbagbar which is still continuing to improve employee performance in managing work. This study aims to examine the effect of the quality of human resources, work environment, and safety on employee performance in the perspective of Human Resource Management. The method used is quantitative with analysis using SPSS 25 program, involving 67 respondents determined by total sampling strategy. The findings showed that partially, the quality of human resources had a negative and insignificant effect on employee performance, while the work environment and Occupational Safety had a positive and significant effect on employee performance in the company. Simultaneously the quality of human resources, work environment, and Occupational Safety have a positive and significant effect on employee performance. The implementation of Human Resource Management in the Regional Office of DJBC Sumbagbar has been based on the principles of Justice (al-adl), Trust (al-amānah), and responsibility (al-Mas'ūliyyah).